Combined microwave-hot air drying optimization and quality analysis of low GI dried taro rounds - Chen Yang; Weiwen Duan; Zhenhua Duan; Aiqing Ren; Yuhong Tian; Liuping Fan (Applied Food Research)
This experiment used taro as a raw material and examined combined microwave-hot air drying to study the effects of various parameters on the quality of dried taro rounds during drying. The effects of microwave power, conversion point moisture content, hot air-drying temperature, and end-point moisture content were studied. The Glycemic Index (GI), sensory score, elasticity, and rehydration ratio of dried taro were used as evaluation indicators. Optimal drying parameters were determined using orthogonal tests, and the quality of dried taro rounds was analyzed using digestion characteristics, texture characteristics, antioxidant capacity, and other indicators. The results showed that the optimal conditions of combined microwave-hot air drying were as follows: microwave power: 350 W, conversion point moisture content: 36 %, hot air-drying temperature: 85 °C, and end point moisture content: 21 %. Under these conditions, the GI of dried taro rounds was 49.87, and the sensory score was 79.33, categorizing it as a low GI food with good sensory quality. The relative contents of slowly digestible starch (SDS) and resistant starch (RS) were 30.96 % and 15.15 %, respectively. Texture characteristics and antioxidant capacity were also improved.